Evaluasi Genotipe Tomat Hasil Iradiasi Sinar Gamma di Dataran Rendah - Romadhon, Muhammad Roiyan; Sutjahjo, Surjono Hadi; Marwiyah, dan Siti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Bacterial wilt and fruit cracking are serious problems in tomatoes cultivation in the lowland area. This research aimed to evaluate the yield of M4 generation of tomatoes in the field and the incidence of bacterial wilt disease and fruit cracking in low altitude. The research was conducted at the IPB Experimental Field in Leuwikopo, Dramaga, Bogor, from December 2015 to April 2016. The experiment used a randomized complete block design with three replications. The material consisted of 15 M4 genotypes and two controls (Berlian and Kefaminano 6). The results showed that genotype of M4/495 Lombok 1-9-2 (U2) has high productivity. Genotype M4/990 Lombok 1-5-1 (U1) has high weight per fruit and resistant to fruit cracking. Genotype M4/495 GL2-8-10 (U2), M4/495 Kemir 1- 4-7 (U3), M4/495 STBGL 1-2-3 (U1) M4/990 Lombok 1-5-1 (U1), and M4/495 STBGL 1-2-9 (U1) have the lowest incidence of bacterial wilt (0.00%). Two genotypes which have high productivity and resistant to fruit cracking are M4/495 Lombok 1-9-2 (U2) and M4/990 Lombok 1-5-1 (U1), and to be evaluated in a preliminary yield trial.